Clinical and demographic profile of patients presenting to cath-lab in a tertiary care center in Nepal - Shrestha, Utsav; Khanal, Subrat; Ghimire, Pranita; Shrestha, Nikesh R (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Coronary Artery Disease (CAD) is one of the leading killers in the world. This is a demographic study of patients who underwent coronary angiography for CAD with regard to sex, age, ethnicity and prevalence of risk factors. Materials & Methods: Hospital based retrospective study conducted at the Department of Internal Medicine, B.P. Koirala Institute of Health Science (BPKIHS), Dharan, Nepal. Results: The Study showed that out of 382 patients who presented to the cath-lab 216 patients underwent angiography alone and 166 patients had PCI. The most common indication for presentation to cath-lab was S-T Elevation Myocardial Infarction (STEMI), which accounted for 46.3% cases. The most common age group of presentation was 51-60 years of age with 35% cases. During the procedure, it was found that 32.8% had normal vessels, 29.6% had single vessel disease and 38% had 2 or more vessels involved. The most common coronary artery involved was left anterior descending (LAD), which was implicated in 96.9 % of total cases. Coronary Artery Disease was defined as having at least one vessel 50% obstructed. A total of 158 males and 99 females had CAD with a sex ratio of 1.59. It was found that 36.1% belonged to Brahmin / Chettri ethnicity whereas 34.0% belonged to Janjati. Hypertension was the most common risk factor, present in 67 % of the patients. Conclusion: It appears that among the population of eastern Nepal, the age group most likely to suffer from an episode of ACS leading to invasive evaluation is between 50 to 60 years. And the most significant risk factors associated are hypertension and smoking. JCMS Nepal. 2015;11(1):1-5